Analisis Manajemen Stratejik dengan Pendekatan Sumber Daya Manusia pada Hotel Grandkemang Jakarta - Rahman Raisuli; Vanessa Azahra Rohman; Akhmad Rasyid Rosidi; Herlina Reva Carita; Muhammad Alzidan Herdiansyah; Ahmad Setiawan Nuraya (Institut Nalanda, 2026)
This study aims to analyze the implementation of strategic management with a human resource approach at Hotel Grandkemang Jakarta in facing increasingly competitive hospitality industry competition. This research used a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, then analyzed using descriptive qualitative and SWOT analysis. The results showed that Hotel Grandkemang implemented Strategic Human Resource Management (SHRM) through routine training, performance evaluation, internal promotion, and employee retention strategies. Employee service quality became the main factor in creating customer satisfaction and maintaining the company’s competitiveness. The study also found several challenges in human resource management, such as employees approaching retirement age, limited regeneration of young workers, and suboptimal technological adaptation. Based on the Resource-Based View (RBV) perspective, Hotel Grandkemang’s human resources possess valuable, rare, inimitable, and non-substitutable characteristics, making them a source of competitive advantage. This study concludes that strategic and sustainable human resource management plays an important role in maintaining service quality and business sustainability in the hospitality industry.